Reduction of Anxiety on Pregnant Women in the 3rd Trimester Through Use of Rosemary Aromatherapy - Purba, Agnes; Christina Roos Etty; Julia Mahdalena; Henny Syapitri (Public Health of Indonesia, 2025)
Background: One of the psychological problems experienced by pregnant women is anxiety. Untreated anxiety will increase the risk of premature birth, miscarriage, cesarean section, and neonatal asphyxia. Aromatherapy as a traditional and natural therapy uses inhaled fragrances and uses plants. One of these aromatherapy is rosemary (Rosmarinus officinalis L.), with minimal side effects, can provide muscle relaxation, relieve anxiety, reduce stress, relax the mind and refresh. Objective: This study aims to analyze the effect of rosemary aromatherapy intervention given by inhalation on anxiety in pregnant women in the third trimester. Methods: The design of this study was a one group pre and post-test design without control. Measurement of respondent anxiety was carried out before and after aromatherapy intervention using the PASS (Perinatal Anxiety Screening Scale). Rosemary aromatherapy was given by mixing 3 drops with 40 ml of water in a diffuser, given before sleep at night. The research sample was healthy third trimester pregnant women who had no history of diseases recorded at the Martine Midwife Clinic as the research location with a total of 53 people. Data analysis used a paired t-test. Results: There is a significant influence on the anxiety of pregnant women in the third trimester before and after using inhalation rosemary aromatherapy (p=0.000). Conclusions: Rosemary aromatherapy (Rosemarinus officinalis L.) can be recommended for use by pregnant women in the third trimester as an effort to overcome anxiety. Keywords: Anxiety; pregnant; rosemary aromatherapy